FDI in Multi-Brand Retailing: A Case Study of Mysore - Mahadevaswamy, G. H.; Nalini, R. (Indian Journal of Marketing, 2013)
The present study was conducted in the city of Mysore to analyze the perceptions of the common man about foreign direct investment (FDI) in multi-brand retailing (MBR). The review of literature evinced the fact that a number of studies have been conducted in the area of FDI in general, and its impact on single brand retail, in particular. There are only a few studies that are available on the impact of FDI in multi brand retailing in India. The major objectives of this study are: (i) to know the perceptions of the common man about FDI in multi-brand retail in India (as the common man’s perceptions on the said topic have been less explored); and (ii) to know the differences in their perceptions. The data required for this study was collected both from primary and secondary sources. Using convenience sampling method, 100 persons were considered as the respondents for the present study. The differences in their perceptions have been analyzed using SPSS to draw meaningful conclusions. The respondents were of the opinion that the impact will be felt on an increase in the general price level supported by an increase in the prices of food products, land, and organized real estate stock prices. However, the respondents were of the opinion that the impact of allowing FDI in MBR will be favorable for the Government and for the producers. To conclude, future studies conducted at the micro level would help policymakers to understand the problems and frame guidelines addressing the critical issues with the major aim of benefiting the society.